2012
DOI: 10.1002/ijc.27495
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic gene therapy with soluble VEGF‐receptors ‐1, ‐2 and ‐3 together with paclitaxel prolongs survival of mice with human ovarian carcinoma

Abstract: We compared effects of antiangiogenic gene therapy with a combination of soluble sVEGFR‐1, sVEGFR‐2 and sVEGFR‐3 to chemotherapy with carboplatin and paclitaxel and to antiangiogenic monoclonal anti‐VEGF‐antibody bevacizumab in an intraperitoneal ovarian cancer xenograft model in mice (n = 80). Gene therapy was also combined with chemotherapy. Therapy was initiated when sizable tumors were confirmed in magnetic resonance imaging (MRI). Adenovirus‐mediated gene transfer was performed intravenously (2 × 109 pfu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…These results are in line with our previous studies with adenoviral gene therapy with sVEGFR-1, sVEGFR-2 and sVEGFR-3 and a clinical study is warranted [27,29]. Survival was significantly prolonged in treatment group II as compared to control group I and other treatment groups (III, IV).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with our previous studies with adenoviral gene therapy with sVEGFR-1, sVEGFR-2 and sVEGFR-3 and a clinical study is warranted [27,29]. Survival was significantly prolonged in treatment group II as compared to control group I and other treatment groups (III, IV).…”
Section: Discussionsupporting
confidence: 89%
“…As in our previous studies [27][28][29] morphologic MRI was used for the timing of gene therapy to treat sizeable tumors, not a micrometastatic disease. Furthermore, non-invasive DW-MRI and relaxation time measurements were used to monitor treatment responses at molecular level in several time points in solid ovarian cancer tumors.…”
Section: Animal Modelmentioning
confidence: 99%
“…Thus far, AdHSV-tk/GCV and AdsVEGFR-1 gene therapies have not been combined for the treatment of MG or any other cancer. AdHSV-tk/GCV has been successfully combined with endostatin gene therapy for the treatment of renal cell cancer (Pulkkanen et al, 2002), while sVEGFR-1 has been combined with oncolytic viruses (Zhang et al, 2005;Guse et al, 2010), other sVEGFRs (Sallinen et al, 2009), soluble Tie2 (Sallinen et al, 2011), and chemotherapy (Sopo et al, 2012). All previous studies with sVEGFR-1 gene therapy for MG were conducted on nude mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…/hum.2013 (Graepler et al, 2005) has shown synergy with sVEGFR-1. Our group has previously demonstrated successful combination of soluble VEGF receptors 1, 2, and 3 (Sallinen et al, 2009;Sopo et al, 2012), and 1 and 3 (Sallinen et al, 2011) with soluble Tie-2 in an ovarian cancer model. Combination with cytotoxic therapy could possibly overcome some of the inherent drawbacks of anti-angiogenic therapy, mentioned before.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation